Development of Articulate Storyline 3 Learning Media for Mathematical Computational Thinking Skills - Santika, Aan; Nisa, Ratu Khoirotun; Nasrullah, Anton; Alfiyanti, Fina; Aminah, Mimih; Dwiyanti, Widya (EDUPEDIA Publisher, 2025)
Mathematical computational thinking skills are essential in mathematics learning, particularly in training systematic problem-solving abilities. However, the limited availability of interactive and effective learning media has remained a significant obstacle to developing these skills. This study aims to develop learning media based on Articulate Storyline 3, which is designed to enhance students' mathematical computational thinking skills. The method employed in this research is Research and Development (R&D) using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were high school students selected through purposive sampling. The research instruments included expert validation questionnaires, user response questionnaires, and tests to assess computational thinking skills. The study results have shown that the developed learning media has achieved a very high level of validity according to evaluations from both material and media experts. Additionally, user responses have demonstrated high satisfaction with the interactivity and ease of media use. Field trials have revealed a significant increase in students' mathematical computational thinking skills after using the learning media. Based on these findings, learning media based on Articulate Storyline 3 has effectively improved mathematical computational thinking skills. These results are expected to contribute positively to more interactive and practical mathematics education innovations.